Teologi Pemujaan Dewa Gede Celak Kontong - Ni Made Evi Kurnia Dewi (Kamaya: Jurnal Ilmu Agama, 2020)
This paper contains the Theology of Worship of Dewa Gede Celak Kontong in Kayuputih Village, Banjar District, Buleleng Regency. This worship is carried out through a medium in the form of Lingga Yoni. The worship of Dewa Gede Celak Kontong in Kayuputih Village has a very important role, especially related to agriculture. Various activities of the Kayuputih Village community related to agriculture are always preceded by the implementation of the worship of Dewa Gede Celak Kontong. The worship was carried out in the hope that the residents' agriculture would be free from all kinds of diseases. Dewa Gede Celak Kontong in Kayuputih Village is worshiped as the God of Fertility, Dewa Gede Celak Kontong in Kayuputih Village is worshiped as the God of Fertility, besides that Dewa Gede Celak Kontong is also believed to be a symbol of safety, birth, human health, and is believed to be a power that provides healing and protection from interference by supernatural beings or from black magic powers. The theology of worship of Dewa Gede Celak Kontong in Kayuputih Village, Banjar District, Buleleng Regency was studied using qualitative descriptive research methods. The data collection techniques used in this research are observation or direct observation, Interview method, and document study. The data analysis techniques used were data reduction, data classification, data display, and conclusion drawing.